Built environment approaches: Extension personnel's preferences, barriers, and facilitators - Balis, Laura E.; Grocke-Dewey, Michelle (Frontiers in Public Health, 2022)
Introduction: Interventions that modify the built environment can increase population physical activity levels and prevent chronic disease. The national Cooperative Extension System is poised to implement built environment approaches (i.e., pedestrian/bicycle infrastructure and enhanced access to physical activity spaces), but implementation strategies (i.e., methods or techniques to move research to practice) are needed to improve uptake. Effective implementation strategies address relevant barriers and capitalize on facilitators. The purpose of this study was to understand 1) barriers and facilitators to implementing built environment approaches in two state Extension systems, 2) preferences for built environment approaches, and 3) preferences for implementation strategies. Methods: A cross-sectional online survey was used to understand Extension personnel's preferences for and barriers and facilitators to built environment approaches through a mixed-methods study design. This work was informed by anthropological inquiry as the overall research philosophy, and by the Health Impact Pyramid, Leeman et al.’s classification of implementation strategies, and the Consolidated Framework for Implementation Research as the theoretical frameworks. The survey was distributed to eligible Extension personnel (n=42) in two states. Quantitative data analysis consisted of numbers/proportions and Friedman tests. Qualitative analysis was completed through a rapid deductive approach to quickly produce actionable results. Results: Fourteen respondents (33%) completed the survey. Most had not implemented physical activity interventions in their communities or had implemented only individual-level interventions, though were interested in implementing built environment approaches . Benches, playground improvements, and crosswalks were the most desired approaches, while facilitation, assessing community strengths and needs , and technical assistance were desired implementation strategies. The most common barriers were relative priority and available resources; facilitators were external policy and incentives and implementation climate. Discussion: Extension personnel are receptive to built environment approaches and engaged with community coalitions. Yet, invested parties prefer individual-level interventions, and agents perceive a lack of resources for implementation. Implementation strategies that build capacity in both the Extension system and community coalitions may address these barriers through increasing relative priority and sharing existing resources. This work is a first step towards compiling implementation strategies to address relevant barriers to built environment approaches in community settings.